Hematologic parameters in thrombocytopenic patients with dengue fever - Aasiya Rajbhandari; Manisha Shrestha; Prakriti Shah; Sushil Adhikari (Journal of Pathology of Nepal)
Background: Dengue fever is an endemic disease in Nepal that has shown increasing incidence each passing year. Dengue has a wide range of clinical presentations and laboratory findings. Thrombocytopenia is a common finding in dengue-infected patients along with other findings like leukopenia, lymphocytosis, raised hematocrit, and elevated liver enzymes. Thrombocytopenia is an indicator of disease severity and can lead to severe bleeding manifestations. This study aims to find the association of thrombocytopenia with other hematologic parameters.